Corporate social responsibility reporting by South African mining companies: Evidence of legitimacy theory - S. Dube; W. Maroun (South African Journal of Business Management, 2017)
This paper offers evidence on the relevance of legitimacy theory for explaining changes in the frequency of corporate social responsibility (CSR) disclosures by South African platinum mining companies following violent strike action during 2012 at Marikana. The results show that all of the South African platinum mining companies provide additional information dealing specifically with the strike taking place at Marikana. This is more pronounced for the company directly involved in the incident. The research also finds evidence of a reaction to the social event by other companies in the South African Platinum Industry which alter the nature and extent of general CSR disclosures to maintain legitimacy. In this way, the study offers evidence in support of the relevance of legitimacy theory for explaining changes in CSR reporting. The findings of this study complement existing research which has ignored the South African market. Although there has been some work on legitimacy theory in the context of environmental disclosure by South African companies, the study is the first to examine a significant social event using legitimacy theory as the frame of reference.
Keywords: 650